Exploring thermocatalytic pyrolysis to derive sustainable chemical intermediates from plastic waste; role of temperature, catalyst, and reactor conditions - Venkataraghavan, R.; Bhure, Arvind; Khan, Tufeil Sartaj; Shikare, Dipak; Devi, R. Nandini; Dhepe, Paresh Laxmikant (Journal of the Indian Institute of Science, 2024)
Plastic waste is a growing concern globally on account of the increasing use of plastic worldwide, compounded by single-use applications, poor waste collection and management practices, and its consequent leakage into the environment. In addition, plastics are derived from non-renewable fossil resources, and their growing demand is also partly responsible for greenhouse gas emissions and climate change. The aim of this paper is to explore the potential of plastic waste as a material resource, and thermocatalytic pyrolysis as a recycling process, to produce aliphatic and aromatic hydrocarbons, which are important chemical intermediates for various industries. We show that plastic pyrolysis can achieve a high yield of liquid hydrocarbons (similar to 80%) with a suitable distribution of aliphatic and aromatic compounds, by using different pyrolysis conditions and a catalyst. Specifically, this paper demonstrates the possibility of deriving two key classes of hydrocarbons, i.e., aliphatic (C10-C20 hydrocarbons) and aromatic hydrocarbons (xylene, toluene and benzene derivatives) with a yield of similar to 80% liquid hydrocarbons via catalytic pyrolysis. We also briefly discuss the challenges and opportunities, and the environmental and economic implications.